Desenvolvimento de plataformas baseadas em alumina e sílica nanoestruturadas com permanganato de potássio para uso como sensor colorimétrico de maturação de tomates cv. Pizzadoro - Ohashi, Thaís Luri (Universidade Federal de São Carlos, 2015)
Fruit quality is closely related to its physical characteristics, such as surface color and firmness, and are directly associated to the ethylene production (C2H4), which is the ripening hormone responsible for initiating the ripening process in fruits and vegetables. Consequently, the control of ethylene levels during postharvest can contribute to effectively extend vegetables shelf life. On the other hand, ripening indicators can be useful for the fruit production chain, because they provide information about product quality and may assist both the wholesaler and the consumer in the purchase decision steps. The aim of this study was to evaluate the functionality of platforms containing potassium permanganate (KMnO4) impregnated into inorganic nanoparticles (alumina and silica). Such platforms are aimed to be used as a colorimetric indicator (sensor) of ‘Pizzadoro’ tomato maturation, relating to the physicochemical changes in fruit quality. The use of nanoparticles (size between 1 and 100 nm) as carriers for KMnO4 makes ethylene oxidation more efficient, and allows for a superior color change, when compared to larger particles (above 100 nm). ‘Pizzadoro’ tomato fruits packed in polyethylene terephthalate packages (PET) containing adhesive with different concentrations of potassium permanganate (2,5%, 5%, 10%) impregnated into nanoparticles were maintained in storage chambers at 22 °C and 90% RH; and evaluated at every two days regarding: peel color, firmness, pH, soluble solids (ºBrix), titratable acidity, maturation index (ratio), as well as the gaseous composition of the package, except for fresh weight loss, which was carried out daily. The results indicated that potassium permanganate impregnated on nanoparticles were capable of absorbing and oxidizing ethylene efficiently, resulting in a gradual color change of the adhesives, from purple to brown. No significant differences in physical and chemical variables between treatments were observed, except for the fruit color parameters, suggesting delayed chlorophyll degradation and lycopene synthesis. Alumina nanoparticles impregnated with 5 and 10% of KMnO4 treatments showed a better performance as maturation indicators, presenting at least three adhesive color standards each. In sensory evaluation, tasters preferred the more intense red coloration fruits.
Keywords: Absorvedor de etileno; Nanopartículas de alumina e sílica; Amadurecimento; Pós-colheita; Qualidade; Ethylene absorber; Alumina and silica nanoparticles; Ripening; Postharvest; Quality; Lycopersicon esculentum Mill; OUTROS